1998
DOI: 10.1126/science.280.5371.1916
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Vegetation-Atmosphere-Ocean Interaction on Climate During the Mid-Holocene

Abstract: surement precisions (0.5%) (20) in the travel times themselves. 20. Single-crystal samples of MgO (purity Ͼ99.9%) were oriented with x-ray diffraction method described in (13) to [100] and [110] orientations (better than 1°); the samples were cored, cut, and polished to cylinders of about 1.8 mm in diameter and 1.2 to 1.5 mm in length. The original sample lengths were measured to micrometers, that is, Ϯ 1 m. Measurements of the sample travel time were achieved by overlapping the glass buffer rod echo and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
190
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 351 publications
(213 citation statements)
references
References 26 publications
20
190
1
2
Order By: Relevance
“…However, given different cloud parameterization schemes across models, it is not obvious why all of the models tend to exhibit a global warming trend bias. Vegetation feedback has been suggested to be able to induce warming in the Early to Mid-Holocene in the mid-to high-latitude boreal forest region through its impact on surface albedo (25). However, the CCSM3 and LOVECLIM both include dynamic vegetation models, which apparently are insufficient to generate a cooling trend in these models.…”
Section: Uncertainty In Climate Modelsmentioning
confidence: 99%
“…However, given different cloud parameterization schemes across models, it is not obvious why all of the models tend to exhibit a global warming trend bias. Vegetation feedback has been suggested to be able to induce warming in the Early to Mid-Holocene in the mid-to high-latitude boreal forest region through its impact on surface albedo (25). However, the CCSM3 and LOVECLIM both include dynamic vegetation models, which apparently are insufficient to generate a cooling trend in these models.…”
Section: Uncertainty In Climate Modelsmentioning
confidence: 99%
“…According to Berger and Loutre [1991], Northern Hemisphere summer solar insolation has been decreasing since the early Holocene. Numerical modeling experiments have shown that a decrease in insolation would have resulted in a weakened monsoon circulation [Ganopolski et al, 1998;Kutzbach et al, 2001]. The forcing mechanism lies in that the cooling of the continental interior gives rise to a decrease in thermal contrast between the east Asian continent and the adjacent ocean, thus leading to a weakened monsoon circulation, i.e., a southeastward retreat of the east Asian summer monsoon.…”
Section: Mid-holocene Drying Inferred From Dolomite Precipitation Andmentioning
confidence: 99%
“…Likewise, a more vegetated land surface appears to be darker than bare soil, which not only increases absorption of solar radiation but also evaporation and, finally, the greenhouse effect. model, a multibasin, zonally averaged ocean model including sea ice, and, in contrast to [Ganopolski et al, 1998a], a dynamic model of terrestrial vegetation [Brovkin et al, 1997[Brovkin et al, , 1999. Vegetation cover is represented as a composition of trees, grass, and desert (bare soil).…”
Section: Climate Simulationsmentioning
confidence: 99%